2016
DOI: 10.1002/mnfr.201600301
|View full text |Cite
|
Sign up to set email alerts
|

Casein glycomacropeptide‐derived peptide IPPKKNQDKTE ameliorates high glucose‐induced insulin resistance in HepG2 cells via activation of AMPK signaling

Abstract: IPPKKNQDKTE prevents high glucose-induced insulin resistance in HepG2 cells by modulating the IRS-1/PI3K/Akt signaling pathway through AMPK activation, indicating that IPPKKNQDKTE plays a potential role in the prevention and treatment of hepatic insulin resistance and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…GMP exerts varieties of biological activities. GMP-derived peptide could prevent high glucose-induced insulin resistance in HepG2 cells via activating the IRS/PI3K/Akt signaling pathway [17]. In addition, hydrolysate of GMP (GHP) increased the level of hepatic glycogen and ameliorated the hepatic insulin resistance of high-fat diet (HFD)-fed mice [18].…”
Section: Of 15mentioning
confidence: 99%
“…GMP exerts varieties of biological activities. GMP-derived peptide could prevent high glucose-induced insulin resistance in HepG2 cells via activating the IRS/PI3K/Akt signaling pathway [17]. In addition, hydrolysate of GMP (GHP) increased the level of hepatic glycogen and ameliorated the hepatic insulin resistance of high-fat diet (HFD)-fed mice [18].…”
Section: Of 15mentioning
confidence: 99%
“…Previous studies have explored alterations in phosphoinositide 3‐kinase (PI3K)/protein kinase B (Akt) signaling, a classical signaling pathway that serves as a key step of receptor signal transduction (Nie et al., 2016), as a major mechanism underlying hypoglycemia (Wang et al., 2019). Hyperglycemia is prolonged by such alterations, which, in turn, worsen insulin sensitivity and aggravate insulin resistance in peripheral tissues (Song et al., 2017). Therefore, ameliorating hepatic insulin resistance may constitute an effective therapeutic strategy for regulating glucose homeostasis and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS production leads to impaired insulin signaling pathway by inducing IRS serine phosphorylation, followed by decreasing GLUT4 translocation . Although several reports suggested that food‐derived peptides could improve insulin resistance, effect of peptides on RAS stimulated insulin resistance in skeletal muscle and their mechanism have yet to be investigated. Egg white is a rich source of various bioactive peptides .…”
Section: Introductionmentioning
confidence: 99%